Reproduction of White-Spotted Rabbitfish (Siganus canaliculatus Park, 1797) in the Waters of the Buntal Island, Kotania Bay, West Seram-Mollucas - Latuconsina, Husain; Lestaluhu, Rospita; Rumasoreng, Risman (Agrikan: Jurnal Agribisnis Perikanan, 2020)
White-Spotted Rabbitfish (Siganus canaliculatus Park, 1797) are herbivorous fish that are associated with seagrass habitat and are widely distributed in mangrove and coral reef habitats. The waters of the Buntal  Island – Kotania Bau have an ecosystem of seagrass medows, mangroves and coral reefs, with the association of S. canaliculatus as one of the target catch of fishermen. The purpose was study to analyze the biological aspects of S. canaliculatus, including: sex ratio, size of first maturity, and fecundity. The research was conducted from October 2015 until January 2016 in the waters of Buntal Island, Kotania Bay. Fish samples were collected from fishermen's catch using bottom gill nets and Set net. Each fish sample was dissected for sex determination and gonad maturity level. The analysis is used to see the relationship between body length and weight and fecundity. The results showed that 167 fish and 149 female fish. The ratio of male and female was balanced, namely 52.85%: 47.15% or 1.1: 1 (X2count 4.13 <X2table 11.34). The size of first maturity of female is 14.98 cm (14.5 - 15.5 cm) smaller than the male 18.9 cm (18.8 - 19.1 cm). The high potential of S. canaliclulatus based on the Fecundity obtained was in the range of 524,000 - 1,286,359 eggs. There is a positive relationship between body length and fecundity, indicating that the value of Fecundity increases with body size. To support its sustainable use in the wild, it is necessary to regulate the size of S. canaliculatus that can be harvest at a body length of > 15 cm TL, to provide opportunities for spawning and support population growth before exploitation, thus supporting responsible and sustainable fisheries.